2023
DOI: 10.1002/ps.7917
|View full text |Cite
|
Sign up to set email alerts
|

The miR‐184‐3p promotes rice black‐streaked dwarf virus infection by suppressing Ken in Laodelphax striatellus (Fallén)

Wei Wu,
Man Wang,
Zhiting Deng
et al.

Abstract: BACKGROUNDMicroRNAs (miRNAs) play a key role in various biological processes by influencing the translation of target messenger RNAs (mRNAs) through post‐transcriptional regulation. The miR‐184‐3p has been identified as an abundant conserved miRNA in insects. However, less is known about its functions in insect–plant virus interactions.RESULTSThe function of miR‐184‐3p in regulation of plant viral infection in insects was investigated using a rice black‐streaked dwarf virus (RBSDV) and Laodelphax striatellus (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 54 publications
0
2
0
Order By: Relevance
“…For example, a small RNA derived from rice stripe virus (RSV) downregulates the miR263a of SBPH and then suppresses RSV infection [ 20 ]. Some researchers found that miR315-5p and miR184-3p could effectively modulate RBSDV infection in SBPH [ 21 , 22 ]. Li et al analyzed the conserved and novel miRNA profiles in RBSDV-infected SBPH and found miR750-3p was downregulated in RBSDV-infected SBPH [ 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…For example, a small RNA derived from rice stripe virus (RSV) downregulates the miR263a of SBPH and then suppresses RSV infection [ 20 ]. Some researchers found that miR315-5p and miR184-3p could effectively modulate RBSDV infection in SBPH [ 21 , 22 ]. Li et al analyzed the conserved and novel miRNA profiles in RBSDV-infected SBPH and found miR750-3p was downregulated in RBSDV-infected SBPH [ 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…In the pea aphid, Acyrthosiphon pisum (Aphididae, Hemiptera) , miR-184 negatively regulates the JNK (Jun N-terminal kinase) signaling pathway, which is involved in the immune response [ 18 ]. Moreover, miR-184 impacts the plant virus–host interactions by regulating the dynamics between rice black streak dwarf virus (RBSDV) and its insect vector, the planthopper Laodelphax striatellus (Delphacidae, Hemiptera), offering insights into pest-mediated virus transmission [ 19 ].…”
Section: Introductionmentioning
confidence: 99%